Statutory auditor's profile and computer assisted audit tools and techniques' acceptance: Indicators on firms and peers' influence - Pedrosa, I.; Costa, C. (ACM International Conference Proceeding Series, 2014)
In this paper, statutory auditors' profiles will be defined on Computer Assisted Audit Tools and Techniques' intention to use and use concerning the influence of statutory auditors firms' dimension (number of collaborators, number of financial auditors and number of statutory auditors), peers impact (other statutory auditors and the professional group influence on the professional context) and social influence (people and firm support). Additionally, previous research on the experience with tools and its influence on the acceptance are documented this research group, and also the professional experience (number of years of professional experience). The variety of computer assisted audit tools available in the firm and its impact on the acceptance is also addressed. In the reference group, was possible to conclude that firm dimension, peers and social influence and experience have a positive impact on Computer Assisted Audit Tools and Techniques' acceptance. However, the number of available tools has a negative impact on intention to use confirming that is not relevant to have several tools but to be expert in one or two tools.